ANALISIS STRATEGI MEDIA SOSIAL DALAM MEMBANGUN BRAND IMAGE (Studi Pada Instagram Fujifilm Indonesia) - Theresia Erlin Christiani (Universitas Mercu Buana, 2020)
Technological developments have an impact on all aspects of life including the world of photography. Photography developed from analog to digital technology, which increased public interest in the world of photography. The development of technology has also been encouraged the emergence of social media as a medium of communication as well as a media for promotion/business over time which has been widely used by companies/business owners. PT. Fujifilm Indonesia is building a new brand image by utilizing Instagram as a means of communication to rebuild consumer trust due to rejection that occurred as a result of the shift in its core business from washing print and roll film to being a digital camera manufacturer. The purpose of this study is to determine the marketing communication strategy applied by Fujifilm Indonesia in building and strengthening their brand image using Instagram. The theoretical concept used in this research is to use Belch & Belch's marketing communication theory which states that to create a marketing communication strategy, it is necessary to go through at least several stages, namely the planning stage to the control stage. This research uses a case study research method with a qualitative approach. This research shows that the use of KOL is proven to be effective in attracting attention and forming consumer trust which is supported by consistency in uploading content and responding to consumers on Instagram.